EVALUASI BESARAN PENGGAJIAN DAN PENGUPAHAN TENAGA KERJA HARIAN LEPAS / OUTSOURCHING PADA PT. BIRUTIGA UTAMA - Elfreda Aplonia Lau., Andi Amansyah Robin Jonathan, (EKONOMIA, 2020)
The purpose of this research is to find out amount of payroll and remuneration for Outsourced / daily workers is applied to PT. Birutiga Utama is in accordance with the application of the amount of payroll and remuneration refers to Law No. 13 of 2003?               Based on the background, formulation of the problem and basis theoretical that has been stated in this thesis, then amount of payroll and remuneration for Outsourching / daily freelancers at PT. Birutiga Utama is not in accordance with the application of the amount of payroll and remuneration refers to Law No. 13 of 2003.               The type of research used is comparative research by comparing the amount of payroll and remuneration for Outsourced / daily freelancers applied to PT. Birutiga Utama with the amount of payroll and remuneration refers to Law No. 13 of 2003.               Based on the research that has been done, it can be concluded that the results of research on the amount of payroll and remuneration applied to PT. Birutiga Utama is does not refer to / does not comply with the rules contained in Law No. 13 of 2003 specifically regarding the amount of payroll and remuneration.